(untitled) (TSUL LEGAL REPORT, 2026)
This article focuses on modern state management and administrative reforms implemented in this field, improvement of public service, development of requirements for modern civil servants. This topic is analyzed on the basis of ongoing legal reforms and legal documents. On the basis of scientific and legal sources, modern state administration, the main functions of civil servants and the mechanisms of their implementation have been scientifically and theoretically researched. Opinions were expressed on the implementation of a unified personnel policy, rules on the elimination of corruption and conflicts of interest in the activities of civil servants, as well as the implementation of digital technologies, meritocracy, and career models in the civil service. Proposals and recommendations have been developed for the improvement of public service.